2005
DOI: 10.1007/s00432-005-0055-7
|View full text |Cite
|
Sign up to set email alerts
|

Solitary fibrous tumor in the thigh: review of the literature

Abstract: Solitary fibrous tumors (SFT) of extremities, especially the thighs are very rare. Despite SFTs are generally benign, well-circumscribed soft tissue tumors new cases should be presented and followed up carefully to monitor their biological behavior. In general for tumor classification a biopsy is state of the art. Histological including immunohistochemical patterns for SFTs are defined. MRI and ultrasound are not sufficient for differential diagnosis. Once property identified and defined by size and location, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…Contrast enhanced MRI shows heterogeneous in as many as 82% of extrapleural SFT cases, and homogeneous enhancement effect in approximately 18%. 16,18,19 In our case, the mass showed very low signal intensity on T2-weighted image. This peculiar aspect could be the result of 30 years of exerted compression on the extrapleural SFT which may have cause hemorrhage, reactive fibroplasia, and/or calcification.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Contrast enhanced MRI shows heterogeneous in as many as 82% of extrapleural SFT cases, and homogeneous enhancement effect in approximately 18%. 16,18,19 In our case, the mass showed very low signal intensity on T2-weighted image. This peculiar aspect could be the result of 30 years of exerted compression on the extrapleural SFT which may have cause hemorrhage, reactive fibroplasia, and/or calcification.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, many authors reported that the majority of these tumors (80%) showed hypointense or isointense on T1-weighted image relative to muscle, and hypointense on T2-weighted image. [12][13][14][15][16][17][18][19] On the other hand, Shin JH et al 20 reported that the extrapleural SFT in the buccal space showed hyperintense on T2-weighted image. Contrast enhanced MRI shows heterogeneous in as many as 82% of extrapleural SFT cases, and homogeneous enhancement effect in approximately 18%.…”
Section: Discussionmentioning
confidence: 99%
“…Cellularity is changeable and mitosis is seen rarely. Anders et al [5] Thigh 41 Wide excision 54 -Thanni [6] Proximal cruris 22 En-bloc resection plus radiotherapy 9 Wound infection Fukui et al [10] 1 shoulder 1 thigh 81-70 Wide excision 24 -9 -Wan et al [1] 3 thigh 1 calf 47.8 Wide excision 65.5 -Chandanwale et al [11] Calf 15 Wide excision 12 Recurrence (12 month) Al-Shanawani et al [20] Arm 30 Wide excision 36 -Yoshimura et al [18] Thigh Malignant tumors are typically hypercellular and contain prominent atypicality, necrosis, too many mitosis (≥4/10 high power field) and irregular infiltrative margins. [15] In immunohistochemical evaluation, tumor cells are characteristically immunoreactive with CD34, vimentin and CD99.…”
Section: Discussionmentioning
confidence: 99%
“…If there are evidences that suggest malignant potential, wide resection together with a long-term follow-up and regular magnetic resonance imaging (MRI) controls are advised. [5] Adjuvant radiotherapy and chemotherapy are recommended for metastases, recurrence and incomplete resection. [6] In this study, we aimed to evaluate the clinical characteristics and treatment results of patients with a diagnosis of SFT localized in extremity.…”
mentioning
confidence: 99%
“…The immunoreactivities of vimentin, Bcl-2, CD 99 and CD34 are important because they can distinguish SFT from other tumors. Anders et al 13) stated CD99 was usually positive, and others like CK, S-100, desmin and SMA were negative. Our patient's results were consistent with the above statement, except that CD34 was negative.…”
Section: )mentioning
confidence: 98%